Thoracic aortic atherosclerosis in patients with a bicuspid aortic valve; a case–control study - Onur B. Dolmaci; Robert J. M. Klautz; Robert E. Poelmann; Jan H. N. Lindeman; Ralf Sprengers; Lucia Kroft; Nimrat Grewal (BMC Cardiovascular Disorders, 2023)
Abstract Introduction Bicuspid aortic valve (BAV) patients have an increased risk to develop thoracic aortic complications. Little is known about the prevalence and severity of atherosclerosis in the BAV ascending aortic wall. This study evaluates and compares the prevalence of thoracic aortic atherosclerosis in BAV and tricuspid aortic valve (TAV) patients. Methods Atherosclerosis was objectified using three diagnostic modalities in two separate BAV patient cohorts (with and without an aortic dilatation). Within the first group, atherosclerosis was graded histopathologically according to the modified AHA classification scheme proposed by Virmani et al. In the second group, the calcific load of the ascending aorta and coronary arteries, coronary angiographies and cardiovascular risk factors were studied. Patients were selected from a surgical database (treated between 2006–2020), resulting in a total of 128 inclusions. Results Histopathology showed atherosclerotic lesions to be more prevalent and severe in all TAV as compared to all BAV patients (OR 1.49 (95%CI 1.14 – 1.94); p = 0.003). Computed tomography showed no significant differences in ascending aortic wall calcification between all BAV and all TAV patients, although a tendency of lower calcific load in favor of BAV was seen. Coronary calcification was higher in all TAV as compared to all BAV (OR 1.30 (95%CI 1.06 – 1.61); p = 0.014). Conclusion Ascending aortic atherosclerotic plaques were histologically more pronounced in TAV as compared to the BAV patients, while CT scans revealed equal amounts of calcific depositions within the ascending aortic wall. This study confirms less atherosclerosis in the ascending aortic wall and coronary arteries of BAV patients as compared to TAV patients. These results were not affected by the presence of a thoracic aortic aneurysm.